Nature of magnetic transitions and evidence for magnetoelastic coupling in the biskyrmion-host hexagonal compound MnNiGa - Singh A.K.; Devi P.; Shahi N.; Dubey K.K.; Singh S.; Pandey D. (My University, 2025)
The hexagonal compound MnNiGa with Ni2In-type structure has emerged as an important biskyrmion-host system in which these textures are super-stable over a wide temperature range extending from 16 K to the Curie temperature TC ∼350 K under moderate fields. Both the intensity of the external magnetic field and the presence of magnetoelastic coupling are known to play key role in the stability of the skyrmionic textures. Here we present the results of the first comprehensive investigation of the order of the phase transitions and its field dependence along with magnetoelastic (i.e., spin-lattice) coupling using a combined magnetization and high-resolution synchrotron x-ray powder diffraction (SXRPD) study of MnNiGa. The temperature dependence of the magnetization M(T) exhibits a paramagnetic to collinear ferromagnetic (FM) transition at TC (∼347 ± 0.5 K) with thermal hysteresis and negative slope in the Arrott plots across the TC suggesting its first order character. The M(T) plot in the collinear FM phase exhibits an anomalously decreasing behaviour after reaching its peak value at 300 K followed by a step-like change below 210 K due to an additional spin reorientation transition (SRT) to a non-collinear FM phase with TSRT∼200 ± 1 K. The SRT also shows thermal hysteresis characteristic of a first order phase transition. Our field dependent studies reveal stabilization of the collinear FM phase to higher temperatures and destabilization of the SRT transition setting an upper limit on the magnetic field for the observation of biskyrmions in this system. The Rietveld analysis of the SXRPD data reveals anomalies in the unit cell parameters at TC and TSRT without any change in the crystal symmetry. The modelling of the temperature dependence of the unit cell volume in terms of the Debye-Grüneisen equation reveals significant deviation from phonon contributions and the presence of the quadratic spin-lattice coupling below the FM TC, in the precursor SRT regime as well as below TSRT. The present results on the magnetoelastic coupling in the hexagonal MnNiGa may provide the necessary insight towards understanding the extreme sensitivity of the magnetic skyrmionic textures to external stresses. © 2023 Elsevier B.V.